1992
DOI: 10.1002/ajhb.1310040204
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional requirements and human evolution: A bioenergetics model

Abstract: A bioenergetics model is developed to examine changes in metabolic requirements over the course of human evolution. Data on (1) body size and resting metabolism, (2) brain size and metabolism, (3) activity budgets, and (4) foraging patterns for humans and other anthropoids are used to evaluate ecological correlates of variation in diet and energy expenditure. Analyses of variation in these extant species provide a framework for estimating (1) resting metabolic requirements, (2) brain metabolic needs, and (3) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
125
1
2

Year Published

1997
1997
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 213 publications
(130 citation statements)
references
References 70 publications
2
125
1
2
Order By: Relevance
“…Although several authors have pointed out that increasing M BR has energetic consequences (10)(11)(12)(13)(14)(15)(16)(17)23), it remained to be determined whether these would indeed be physiologically relevant to the extent of actually making metabolic cost a limiting factor in brain evolution. By using a simple model of scaling of energetic intake and expenditure with increasing M BD and number of brain neurons, here we demonstrate that, for primates feeding exclusively on a raw diet, metabolism is indeed a physiologically relevant limiting factor in evolution such that a tradeoff between M BD and number of brain neurons is imposed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although several authors have pointed out that increasing M BR has energetic consequences (10)(11)(12)(13)(14)(15)(16)(17)23), it remained to be determined whether these would indeed be physiologically relevant to the extent of actually making metabolic cost a limiting factor in brain evolution. By using a simple model of scaling of energetic intake and expenditure with increasing M BD and number of brain neurons, here we demonstrate that, for primates feeding exclusively on a raw diet, metabolism is indeed a physiologically relevant limiting factor in evolution such that a tradeoff between M BD and number of brain neurons is imposed.…”
Section: Discussionmentioning
confidence: 99%
“…The brain is the third most energy-expensive organ in the human body, ranking in total organ metabolic cost below only skeletal muscle and liver (9). Accordingly, several studies have suggested that the main constraints to increasing primate brain size in evolution are metabolic in nature (10)(11)(12)(13)(14)(15)(16)(17)(18). The human brain, in particular, has come to cost āˆ¼20% of the total body resting metabolic rate, even though it represents only 2% of total body mass (M BD ), whereas, in other primates, the brain consumes a lower percentage of the body resting metabolic rate of approximately 9% (17).…”
mentioning
confidence: 99%
“…The average PAL of paleolithic humans was estimated to be approximately 1.8 (range 1.6-2.0: Leonard and Robertson, 1992;Cordain et al, 1998). Based on these epidemiological and paleolithic data, Yamauchi et al concluded that it is reasonable to consider a PAL of 1.75-1.80 as the desired level of daily physical activity (Yamauchi et al, 2004).…”
Section: Comparison With Previous Studies Of Sumo Wrestlersmentioning
confidence: 99%
“…According to FAO (2001), a lifestyle with a PAL value of 1.70-1.99 is classified as an active or moderately active lifestyle, and that of 2.00-2.40 as a vigorous or vigorously active lifestyle. Leonard and Robertson (1992), who studied the bioenergetics of primates from the evolutionary viewpoint, described the PAL values of two hunter-gatherer groups as 1.71 for males and 1.51 for females of the !Kung and 2.15 for males and 1.88 for females of the Ache. The PAL value of the Baka is higher than that of the !Kung and seems to be comparable to that of the Ache.…”
Section: The Paleolithic Foraging Lifestyle In the African Tropical Rmentioning
confidence: 99%